The effects of neuroticism on pair programming: an empirical study in the higher education context - Salleh, Norsaremah; Mendes, Emilia; Grundy, John; Burch, Giles St. J (ACM Press, 2010)
This paper describes a formal experiment carried out to investigate the effect of the personality factor Openness to experience on the academic performance of students who practiced pair programming (PP) in higher education. The experiment was carried out at the University of Auckland, using as subjects undergraduate students attending an introductory software programming course. Our results showed that differences in Openness level could significantly affect academic performance of students who pair programmed. In addition, our results also showed that most students gained higher satisfaction from the PP experience and their confidence level in solving programming exercises was also high.